ผลของการบำบัดด้วยการแก้ปัญหาต่อพฤติกรรมเสี่ยงในการเสพซ้ำของผู้ป่วยติดสารแอมเฟตามีน - พุทธชาด ศรีสุวรรณ์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Presently, one third of patients with amphetamine dependence have relapsing behavior that leads to chronic addiction and psychotic disorders. This study was quasi – experimental research that aimed to investigate the effects of problem solving therapy on relapse risk behaviors among patients with amphetamine dependence. Participants consisted of 48 amphetamine relapsing patients who received treatment at the In-patient Department, Suan Prung Psychiatric Hospital, Chiang Mai province. The instruments consisted of 1) Personal Information Questionnaires 2) The Alcohol, Smoking and Substance Involvement Screening Test – Amphetamine-type stimulants (The ASSIST-ATS) and 3) The Problem Solving Therapy Program developed by the researcher based on the concept of D’Zurilla & Nezu (1982, 2010). This program consisted of six sessions, 60 - 90 minutes each time, 3 times a week. Data were analyzed by descriptive statistics means, t-test dependent and t-test independent. Results of the research revealed that: 1. Mean scores of relapsing risk behaviors among the experimental group at 3 months after treatment (x ̅=12.00, SD=7.95) were statistically significantly lower than before (x ̅=24.58, SD=6.12) (p <.01). 2. Mean scores of relapsing risk behaviors between the experimental (x ̅=12.00, SD=7.95) and control group (x ̅=12.42, SD=8.95) at 3 months after treatment were not different. But the scores of problem-solving skills among the experimental group (x ̅=65.92, SD=5.49) at 3-months after treatment were statistically significantly higher than those of the control group (x ̅=62.50, SD=5.08) (p <.05). The results of this study show that the Problem Solving Therapy Program can increase problem -solving skills and reduce relapsing risk behaviors of patients with amphetamine dependence. Therefore, this program should be used for patience with amphetamine dependence to reduce relapsing risk behaviors.